Factors contributing the effectiveness in public relation practices / Faten Aisyah Ahmad Ramli and Muhammad Faizal Samat - Ahmad Ramli, Faten Aisyah; Samat, Muhammad Faizal (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2018)
To achieve a big success, an organization must emphasis on effectiveness in its practices especially in significant areas such as public relations. To maintain the relationship between an organization and its public, many factors must be recognized. This study explores what factors will contribute in the process of gaining effectiveness in public relations practices. To collect primary data, the researcher had disseminated 384 sets of questionnaires to 384 respondents in Kuala Terengganu and used SPSS version 20 to analyze the data. The finding shows that 4 factors (attitude, trust, skills, and control mutuality) are closely related to effectiveness in public relations practices. However, only attitude and skills affect effectiveness in public relations practices.